QTL mapping analysis of maize plant type based on SNP molecular marker - Zhu, Weihong; Zhao, Yikun; Liu, Jingbao; Huang, Lu; Lu, Xiaomin; Kang, Dingming (Cellular and Molecular Biology, 2019)
In this study, the elite maize inbred line (Zheng683-1) was used as a recurrent parent and the four maize inbred lines (ZPH1388, ZPH5, Dong 237 and Chang 7-2) were used as donor parents. The four F1 hybrids were produced by crossing between them and were continued backcrossing to the recurrent parent to produce four BC3F1s. The BC3F1 were pollinated by selfing four generations to generate the recombinant inbred lines (BC3F5) that showed variation in plant height, ear height, leaf angle. There were 53 lines for Zheng683-1 x ZPH1388, 53 lines for Zheng683-1 x ZPH5, 48 lines for Zheng683-1 x Dong237 and 61 lines for Zheng683-1 x Chang 7-2. The four populations were genotyped by using SNP marker and identified the QTLs of targeted traits by using QTL IciMapping V4.1 software and stepwise regression analysis. The main results are as follows:1. 19 additive QTLs and 2 dominant QTLs about plant height were detected in four introgression lines, and 7, 4, 5, 5 QTLs related plant height in ZPH1388-IL, ZPH5-IL, Dong237-ILand Chang7-2-IL. Among the 21 plant height QTLs, the largest contribution to phenotypic variation was QTLqPHa12 from Dong237-IL population, which evaluated 43.44% of the phenotypic variation of plant height . Followed by qPHa3 from ZPH1388-IL, the phenotypic contribution rate was 20% 2. Sixteen QTLs related ear height were detected in the population of the 4 introgression lines, of which there were 15 additive and 1 dominant QTLs. In addition, 9, 3, and 4 QTLs were detected in ZPH1388-IL, ZPH5-IL and Dong237-IL respectively. Among the 16 ear height QTLs, the largest contribution to phenotypic variation was QTL (qEHa1) from the ZPH1388 IL, which recorded the phenotypic variation of ear height by 26.01%. Next the phenotype contribution rates were 22.05% and 21.46%, respectively for qEHa13 and qEHa15 from Dong237-IL. Fourteen QTLs related leaf angle was detected in the population of the introgression lines, of which there were 5 additive QTLs and 9 dominant QTLs. Moreover, 2, 9, and 3 QTLs were detected in ZPH1388-IL, ZPH5-IL, Dong237-IL, respectively. Among the 14 leaf angle QTLs, the largest contribution to phenotypic variation was QTL (qLAa4) from the Dong237-IL then qLAa3 from ZPH5-IL, detecting the phenotypic variation of leaf angle of 28.56% and 24.08%, respectively.The results showed that the QTL locus was characterized by uneven chromosome distribution. The chromosome 1, 2, 5, and 7 are the regions with the QTL concentrated distribution of plant type traits. The QTL of plant type also showed QTL concentrated distribution in some regions of chromosomes. For example, there are three QTLs about plant height and ear height in the region of chromosome bin1.02, three QTLs about plant and ear heights, as well as leaf angle in the region of chromosome bin 2.02. These areas are QTL enrichment region (or the hot spots) of the pleiotropic gene loci related the plant type and ear traits.